Energy savings measurement and verification through awareness program in an educational building campus / Rijalul Fahmi Mustapa ...[et al.] - Mustapa, Rijalul Fahmi; Dahlan, N. Y.; Mohd Yassin, Ihsan; Nordin, A. H. M. (UiTM Press, 2018)
Energy conservation measures (ECM) is a strategy taken to achieve efficient electrical energy utilization. Two main ECM strategy is retrofitting old inefficient loads or through awareness programme and the energy saved is being calculated through baseline energy models. Energy service company (ESCO) is in the helping hands towards retrofitting old unefficient loads without any upfront payment with the establishment of energy performance contract (EPC). There are certain problems and issues arise pertaining to baseline energy models and EPC through ESCO respectively. Baseline energy models is always associated with problems on selection of the variables that affect the energy consumption for prediction purpose. EPC payback period from the achieved savings may create legal issues and bureaucracy on the terms and aggrement. Thus there are two main intention of this paper which is to investigate the variables that affecting energy consumption through single and multiple regression model and to calculate energy savings from ECM through awareness as an alternative to retrofitting old unefficient loads. Results show that multiple regression model have higher coefficient of determination value and from the ECM that have been conducted, it can be seen that energy savings through awareness programme is achievable. It is hoped that from this work, baseline energy models can be developed with the important variables for prediction purpose and awareness program can be implemented as an alternative for retrofitting program to achieve energy savings with hassle free of legal issues and bureaucracy.